More than meets the eye: The role of microglia in healthy and diseased retina - Murenu, Elisa; Gerhardt, Maximilian-Joachim; Biel, Martin; Michalakis, Stylianos (Frontiers in Immunology, 2022)
Microglia are the main resident immune cells of the nervous system and as such they are involved in multiple roles ranging from tissue homeostasis to response to insults and circuit refinement. While most knowledge about microglia comes from studying the brain population, some mechanisms have been confirmed also for microglia cells in the retina, i.e., the light-sensing compartment of the eye responsible for the initial processing of visual information. However, several key pieces of this puzzle are still unaccounted for, as the characterization of retinal microglia has long been hindered by the reduced population size within the retina as well as the previous lack of technologies enabling single-cell analyses. Accumulating evidence indicates that the same cell type may harbor a high degree of transcriptional, morphological and functional differences depending on its location within the central nervous system. Thus, studying the roles and signatures adopted specifically by microglia in the retina has become increasingly important. Here, we review the current understanding of retinal microglia cells in physiology and in disease, with particular emphasis on newly discovered mechanisms and future research directions.